Online Shopping As Economic Digital Turnover: Household Determinant Analysis in Bengkulu Province - Nopiah, Ririn; Barika, Barika; Apriyanti, Cikit (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
Digital technological transformation impacts providing digital markets for consumers to make shopping easier through marketplaces. The rise of the marketplace plays a big role in driving digital disruption and changing consumer behavior toward purchasing goods and services in digital markets. This research aims to analyze the determinants of online shopping in Bengkulu Province at the household level. This research uses SUSENAS 2022 microdata with household analysis units in Bengkulu Province. The analytical method used is logit-probit regression analysis because the dependent variable is dummy. The research results show that marital status, gender, age, and online loans negatively and significantly affect individuals’ or households' opportunities for online shopping. In addition, productive age, education, employment status, number of households, and level of welfare positively and significantly influence the opportunities for individuals and households to online shopping. Meanwhile, a person's civil servant status does not have a significant influence. This research provides novelty in the form of a level of analysis carried out at the individual and household level through national socio-economic survey data (SUSENAS) for Bengkulu Province and the accuracy of using analytical methods.